2003
DOI: 10.5713/ajas.2003.1443
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Grain Processing and Dietary Protein Degradability on Nitrogen Metabolism, Energy Balance and Methane Production in Young Calves

Abstract: Crossbred (Bos taurus×Bos indicus) calves were used from birth till 14 weeks of age to evaluate three sources of protein that differed in ruminal degradability viz. groundnut cake alone (HD) or in combination with cottonseed meal (MD) and meat and bone meal (LD), when fed along with two sources of non-structural carbohydrates viz. raw (R) and thermally processed (P) maize. Twenty four new born calves were arranged in six groups in a 3×2 factorial design and fed on whole milk up to 56 d of age. All the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
(35 reference statements)
5
10
0
Order By: Relevance
“…Unless optimal ratio between RUP and RDP is ensured, the optimal rumen ecosystem activity cannot be obtained. In our study, decreasing DM, CP, NDF and ADF digestibilities trend was noticed with increasing Findings of the current study indicated that higher dietary RUP resulted in decreased N excretion and were concordant with findings of other workers (Pattanaik et al, 2003;Paengkoum et al, 2004) who reported an increase in N balance and reduction in N excretion when high dietary RUP was fed to ruminants. In the present study, RUP55 diet excreted less urinary N (P<0.05) than RUP25, RUP35 and RUP45 diets.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Unless optimal ratio between RUP and RDP is ensured, the optimal rumen ecosystem activity cannot be obtained. In our study, decreasing DM, CP, NDF and ADF digestibilities trend was noticed with increasing Findings of the current study indicated that higher dietary RUP resulted in decreased N excretion and were concordant with findings of other workers (Pattanaik et al, 2003;Paengkoum et al, 2004) who reported an increase in N balance and reduction in N excretion when high dietary RUP was fed to ruminants. In the present study, RUP55 diet excreted less urinary N (P<0.05) than RUP25, RUP35 and RUP45 diets.…”
Section: Discussionsupporting
confidence: 81%
“…The urea can be recycled into the rumen and becomes again available for conversion into microbial protein. Diets having an increased RUP concentration resulted in improved N balance and decreased N excretion relative to intake (Pattanaik et al, 2003;Reynal and Broderick, 2005). An appropriate balance between ruminally degradable and undergradable protein fractions can assure sufficient amount of required AAs balance for intestinal absorption to match animal's requirement.…”
Section: Discussionmentioning
confidence: 99%
“…In another study (Kumar et al, 2005) CP, DM and NDF digestibility increased with increasing dietary RUP of CP from 41 to 48%. Similar findings were also reported by Pattanaik et al (2003) in calves where NDF digestibility enhanced by increasing RUP level from 45 to 51% of dietary CP. This increased CP and NDF digestibility might be attributed to decreased dietary RDP which ultimately leads to increased ruminal pH (Bodine et al, 2000).…”
Section: Resultssupporting
confidence: 78%
“…In Holstein Friesian cows, different dietary RDP levels based on soybean meal resulted in same excretion of N in milk and feces but increased urinary N in early to mid-lactation period (Castillo et al, 2001). Similarly, increased N retention was also observed in calves when dietary RUP level increased from 45 to 51% of CP (Pattanaik et al, 2003). The reduced urinary N excretion by animals fed diets containing higher level of RUP might reduce ruminal ammonia.…”
Section: Resultsmentioning
confidence: 68%
“…Highest N balance in bulls fed C diet was due to its low RDP level (50%). Higher N retention in crossbred calves fed low RDP diet than those fed high RDP diet was reported by Pattanaik et al (2003). Linear decrease in fecal and urinary N was due to linear decrease in N intake.…”
Section: Discussionmentioning
confidence: 69%